2021
DOI: 10.18231/j.ijn.2021.027
|View full text |Cite
|
Sign up to set email alerts
|

Computational intelligence in subthalamic nucleus deep brain stimulation: Machine learning unsupervised PCA tracking method and clustering techniques for Parkinson`s

Abstract: Deep brain stimulator (DBS) is effectual in plummeting basic fundamental motoric-feature manifestations (i.e., signs and symptoms or syndromes) in Parkinson disease (PD). Yet, a scientific-objective method for quantifying its value is underprovided. We present a machine learning based unsupervised mathematical latent variate factorial (or factor) statistical signal processing based principal component analysis (PCA) tracking cluster method for computing the outcome of induced brain stimuli deep into PD by expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…3,4 But prognostics and computational observations have shown that the success of STN-DBS varies profoundly in setting the DBS electrodes through superior accuracy obsessed by the sensori-motor zone of s-nuclei corresponding to the dorso lateral base portion-of-nucleus. [5][6][7][8][9] The somatotopic scenario of sensorimotor zone in STN plus it is relative to movement and tremor in Parkinson subjects has been highly instituted. 10,11 MER gives the correction position of the STN and based on MER signal patterns (signatures), the STN is identified and implanted DBS electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 But prognostics and computational observations have shown that the success of STN-DBS varies profoundly in setting the DBS electrodes through superior accuracy obsessed by the sensori-motor zone of s-nuclei corresponding to the dorso lateral base portion-of-nucleus. [5][6][7][8][9] The somatotopic scenario of sensorimotor zone in STN plus it is relative to movement and tremor in Parkinson subjects has been highly instituted. 10,11 MER gives the correction position of the STN and based on MER signal patterns (signatures), the STN is identified and implanted DBS electrodes.…”
Section: Introductionmentioning
confidence: 99%